Determination of Hexamine in the Dithane DG fungicide using capillary isotachophoresis - Martinková, Zdeňka; Bartoš, Martin; Mikysek, Tomáš; Švancara, Ivan (Univerzita Pardubice, 2011)
In this article, hexamine (HX; syn.: urotropine, chem.: 1,3,5,7- tetraaza-tricyclo [3.3.1.13,7]decane, C6H12N4) is the analyte of interest determined in commercially marketed fungicide (Dithane DG) with the aid of capillary isotachophoresis. After method development, the optimal electrolyte system comprised 0.01 M KOH + 0.02 M acetic acid + 0.1 % hydroxyethylcellulose (pH 4.75) as the leading electrolyte and 0.01 M acetic acid as the terminator. The calibration / detection characteristics are as follows: linearity over the concentration range of 0– 200 mg.l-1 HX, limit of detection ca. 2 mg.l-1, limit of quantification of ca. 6 mg.l-1 HX. Furthermore, relatively simple procedure (involving extraction as the only major sample pretreatment), low operational costs, and sufficient sensitivity are also typical attributes of the method that can be recommended for analysis of hexamine in herbicides and related samples.
Keywords: capillary isotachophoresis; hexamine (urotropine); Dithane DG fungicide; determination